Strategic Customer Engagement and Conditional Loyalty in Herbal E-Commerce: An Ethical SDL Perspective - Abdul Rohman; Andreas Cahya U.R.P Saragih; Sosidah Sosidah; Selamet Riyadi (PT. Anagata Sembagi Education, 2025)
Indonesia’s herbal e-commerce market presents a distinctive paradox: while exhibiting steady annual growth of 6.2% within the global wellness economy, the ecosystem grapples with a structural trust deficit stemming from the prevalence of product adulteration. Through the lens of Service-Dominant Logic (SDL), this qualitative interpretive study investigates how strategic engagement shapes loyalty within this high-risk context. Drawing on in-depth interviews with 18 consumers and sellers, the analysis demonstrates that successful market actors navigate this deficit not through transactional efficiency, but through Ethical Resource Integration establishing regulatory compliance as a moral value proposition—and Developmental Engagement, a mechanism that elevates consumer health literacy. This interaction fosters heteropatric value co-creation, culminating in a distinct state of Conditional Loyalty: a vigilant adherence where emotional attachment is contingent upon continuous safety validation. Theoretically, this study extends SDL by positioning ethical capabilities as critical antecedents to engagement in regulated health markets. From a managerial perspective, the findings suggest that sustainable value arises less from price competition and more from the seller's evolution into an ethical health advisor within a multi-actor governance ecosystem